Glycemic and Insulinemic Response of Different Types of Jordanian Honey in Healthy and Type 2 Diabetic Volunteers - Abu Rajab, Alia M.; Takruri, Hamed R.H.; Mishal, Aly A.; Alkurd, Refat A. (Pakistan Journal of Nutrition, 2017)
Objective: This study aimed to evaluate the Glycemic Index (GI) and Insulin Index (II) values of some types of Jordanian honey. Materials and Methods: Six types of honey (citrus, locust pod, Spanish thistle, Christ thorn, mixed flora and sugar honeys) were compared with white bread and sucrose for their glycemic and insulinemic responses, using analysis of variance and pair t-test. The investigation was done on 14 healthy and 9 type 2 diabetic volunteers. Results: In healthy volunteers, all types of honey induced lower GI values compared to sucrose and white bread. The GI values of Christ thorn honey (45.4%) and sugar honey (50.8%) were significantly lower (p